Functional analysis of the citrate activator CitO from Enterococcus faecalis implicates a divalent metal in ligand binding - Victor S. Blancato; Victor S. Blancato; Fernando A Pagliai; Christian eMagni; Claudio Fabricio Gonzalez; Graciela L Lorca (Frontiers in Microbiology, 2016)
The regulator of citrate metabolism, CitO, from Enterococcus faecalis belongs to the FCD family within the GntR superfamily. In the presence of citrate, CitO binds to cis-acting sequences located upstream of the cit promoters inducing the expression of genes involved in citrate utilization. The quantification of the molecular binding affinities, performed by isothermal titration calorimetry (ITC), indicated that CitO has a high affinity for citrate (KD= 1.2±0.2 µM), while it did not recognize other metabolic intermediates. Based on a structural model of CitO where a putative small molecule and a metal binding site were identified, it was hypothesized that the metal ion is required for citrate binding. In agreement with this model, citrate binding to CitO sharply decreased when the protein was incubated with EDTA. This effect was reverted by the addition of Ni2+, and Zn2+ to a lesser extent. Structure-based site-directed mutagenesis was conducted and it was found that changes to alanine in residues Arg97 and His191 resulted in decreased binding affinities for citrate, as determined by EMSA and ITC. Further assays using lacZ fusions confirmed that these residues in CitO are involved in sensing citrate in vivo. These results indicate that the molecular modifications induced by a ligand and a metal binding in the C-terminal domain of CitO are required for optimal DNA binding activity, and consequently, transcriptional activation.